Kajian Beberapa Sifat Kimia Tanah Ultisols Pada Tanaman Kelapa Sawit Di Desa Tebedak Kecamatan Ngabang Kabupaten Landak - Sumarno, Sumarno; Suswati, Denah; Hayati, Rita (Jurnal Sains Mahasiswa Pertanian, 2019)
Agricultural field especially in the cultivation of crops, soil conditions and management are important factor that will determine the growth and yield of crops cultivated. In Indonesia, the Ultisols are generally not well handled. On a large scale, the land of Ultisols has been utilized for oil palm plantations, rubber and industrial crop forests, but on the scale of farmer economic constraints is one of the causes of unmanaged soil is well. The province that has a Ultisols spread very widely is East Kalimantan 10.04 million ha, west Kalimantan 5.71 million ha, central Kalimantan 4.81 million ha and Riau 2.27 million ha. The problem faced is the limitation of fertile land and lack of information about the condition of land, to increase production of oil palm in the village Tebedak District Ngabang Regency Landak, it is necessary to study some properties of soil chemistry So that from this research can provide fertilizing advice.This research aims to study some of the chemical properties of the Ultisols soil which are planted with palm oil in several gardens and suggested of Nitrogen, phosphorus and Potassium in village Tebedak District Ngabang Regency Landak. This research is expected to provide information on chemical properties of soil in village Tebedak District Ngabang Regency Landak. The parameters in this study is the reaction of the soil (pH), organic carbon, total nitrogen, phosphorus and potassium available, interchangeable, calcium, magnesium can be exchanged, cation exchange capacity, base saturation, soil texture, and bulk density.The taking of soil samples taken at Palm Gardens in the village Tebedak District Ngabang Regency Landak, soil samples were taken at 5 different Palm locations, each location taken 5 point diagonally and made the composite sample of 1 so that composite samples obtained 5 were analyzed in the laboratory of chemistry and soil fertility Faculty of Agriculture University of Tanjungpura. The results of the analysis of the soil samples in the laboratory showed that a soil pH range from 3,93-4,12 with criteria very wry, organic carbon ranges 0,54-1,07% with low to very low criteria, total nitrogen range 0,07-0,14% with low criteria to very low, phousphorus available range is 20.12-25,55 ppm criteria are, potassium range 0,06-0,12 cmol(+)kg-1 criteria of low to very low, calcium range 0,17-0,31 cmol(+)kg-1 with very low criteria, magnesium range 0,06-0,13 cmol(+)kg-1 with very low criteria, cation exchange capacity ranged 4,58-6,50 cmol(+)kg-1 criteria of low to very low base saturation ranges, 8,73-11,09% with a very low criteria, soil texture in sandy loam and bulk density I deeper 0-30 has the value 1, 32-1,36 g/cm3. Key Words : Oil Palm, Chemical Properties Of The Soil, Ultisols